PERUBAHAN SOSIAL DI KAWASAN BENDA CAGAR BUDAYA SANGIRAN: STUDI TENTANG PERUBAHAN PERILAKU - Bambang Soelistyanto (BRIN, 1996)
This paper will try to discuss the social changes that have occurred in Krikilan Village, Kalijambe District, Sragen Regency, Central Java Province. This village is located in the Sangiran Cultural Heritage Area (BCB) which is protected by law. This is raised in this paper, due to a unique process of social change that only applies in this village. Since this IDT village was visited by foreign researchers especially von Koenigswald in 1934 in the context of exploring the Sangiran Site, followed by the establishment of the Sangiran Museum in 1974, and then followed by the expansion of the rock industry center (fossil) in 1980, social changes are very much found in the life of the people of Krikilan Village.